Data on environmental analysis of natural antioxidant production from walnut husk by a solar photovoltaic-driven system as a replacement for potentially carcinogenic synthetic antioxidants - Khounani, Zahra (Data Brief, 2019)
In order to develop a product sustainably, multiple analyses, including comprehensive environmental assessment, are required. Solar-assisted production of walnut husk methanolic extract (WHME) as a natural antioxidant for biodiesel was scrutinized by using the life cycle assessment (LCA) approach. More specifically, the environmental sustainability of WHME antioxidant was evaluated and compared to that of propyl gallate (PG), the most widely used synthetic biodiesel antioxidant, under two scenarios. Additionally, supplementary files including the inventory data consisting of raw data as well as elementary flows, mid-point, and end-point categories are presented. The analysis of scenarios revealed that the use of the natural antioxidant and the avoidance of the chemical antioxidant in biodiesel fuel could be regarded as an eco-friendly approach substantially enhancing the environmental friendliness of biodiesel in particular in terms of human health. Furthermore, given the waste-oriented nature of WHME, the scenario involved its application could serve as a promising strategy to simultaneously valorize the agro-waste and generate a value-added product; a move toward implementing the circular economy approach in the biodiesel industry.